STUDENTS' MATHEMATICAL CREATIVE THINKING PROFILE IN ALGEBRA OLYMPIAD PROBLEMS THROUGH PROJECT-BASED ASSESSMENT: A QUALITATIVE CASE STUDY - Ali Syarifudin; Sikky El Walida (RADJA PUBLIKA, 2026)
Mathematical creative thinking is a higher-order thinking competency that is essential in developing mathematics olympiads because it requires the ability to produce non-routine solutions flexibly, originally, and elaborately. This study aims to describe in depth the mathematical creative thinking profile of students on the mathematics olympiad team at the junior high school level through the application of project-based assessment on the subject of algebra olympiads. The study used a qualitative descriptive approach with a case study design. The research subjects consisted of three students on the mathematics olympiad team who were selected purposively. Data collection was carried out through open-ended algebra tests, project assignments, observations, and semi-structured interviews. Data analysis focused on four indicators of mathematical creative thinking: fluency, flexibility, originality, and detail, with data validity maintained through triangulation of techniques and assessors. The results showed that each subject had a different mathematical creative thinking profile. Project-based assessment was able to facilitate the emergence of a variety of solution strategies, original solutions, and reflection on the mathematical thinking process, especially in students who were actively involved in the project implementation. These findings provide an empirical contribution to the development of authentic assessment in the context of developing mathematics olympiads and enrich the study of mathematical creative thinking in algebraic material.